PEMANFAATAN KACANG TUNGGAK (Vigna unguiculata) DITAMBAH AIR SIWALAN (Borassus flabellifer) SEBAGAI BAHAN BAKU PEMBUATAN KECAP - Siti Miftahul; Tatang Sopandi (FMIPA : Universitas PGRI Adi Buana, 2016)
This study aims to prove that cowpea can be used as raw material for the manufacture of soy sauce. Materials used are 200 g / L cowpea without water siwalan and 250, 300, 350, 400, 450 g of cowpea with palm 300 ml of water and added water up to a volume of 1 liter with the same fermentation time is 1.5 months , This research was conducted by completely randomized design, test protein and reducing sugar levels were tested using one-way ANOVA, followed by Least Significant Difference Test at test level 0:05. Organolpeptik test uses 8 semi-trained panelists, the data obtained are transformed to log + ½ further tested using one-way ANOVA and Least Significant Difference test continued at test level 0:05. Results of this study indicate that the use of various concentrations of cowpea no significant effect (P> 0.05) on the soy protein content. The use of cowpea 250 g / L plus water siwalan significant effect on reducing sugar. Flavor of soy sauce made from 200 g / L of cowpea with no added water palm and 250-400 g / L cowpea plus water siwalan panelists disliked. The color of soy sauce made from 200 g / L of cowpea with no added water palm and 250-400 g / L cowpea plus water siwalan preferred by the panelists. The aroma of soy sauce made from cowpea 200 g / L is preferable to the aroma of soy sauce made of 250-400 g / L cowpea plus water palm. Keywords: soy sauce, cowpea, siwalan water, protein, sugar reduction